Analyse cartographique transfrontalière de la démographie à la frontière sud du Brésil - Bruno de Oliveira Lemos; Antonio Paulo Cargnin; Suzana Beatriz de Oliveira; Ana Maria de Aveline Bertê (Confins)
This analysis aims at analyzing the behavior of territorial and demographic dynamics in the southernmost federation unit of Brazil, Rio Grande do Sul State, and in neighboring countries, Uruguay and Argentina. Based on previous studies conducted for the State, in which the intensification of the effects of demographic transition and the emptying of the border region were verified, this article sought to identify similarities in neighboring countries and discuss the possible causes of these dynamics. Data analysis showed that the sharp drop in population growth also strongly affects Uruguay, where the population tends to move to the southern coastal fringe, in the departments of Maldonado, Canelones and San Jose. In Argentina, this trend is less intense, except for Misiones, that has attracted population